PROSPEK PARIWISATA MOROTAI - Natan, Nurdin (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
The development of tourism in a region into an object or area of tourism needs to pay attention to the potential of the area concerned in this case the District of Morotai Island, in order to create advantages that comparative in the area, that will be developed include the category still a novice compared to other regions which is much more advanced, with a competitive advantage that is difficult rivaled by other areas. Tourism is the destination where tourists mencanegara maupu domestek melakuakan series of activities directly into one of the excellent for countries to improve their income sources outside of oil and gas and taxes. Currently Indonesia as a developing country in the field of tourism began to promote the country in order to attract the eyes of the world. Morotai is one area that has a sale value in the field of tourism related to him, the central government manjadikan Morotai as a regional tourist destination. Tourism destination is a series of activities carried out by foreign tourists and domestic that directly touch and involve the community so as to bring the economic impact on local communities. Keywords : Morotai Tourism Prospects, Products, Productivity, Human Resources and Marketing